The alloys of iron and copper - Gregg, J. L. (Alloys of iron research. Monograph series, 1934)
Introduction - Constitution of iron-copper alloys - Constitution of iron-copper-carbon alloys - Melting and working of copper irons and steels - Effect of copper on characteristics and physical properties of iron and steel - Precipitation hardening of copper steels - Mechanical properties of iron-copper alloys, copper-bearing wrought iron, and cast steel - Mechanical properties of wrought copper steels - Corrosion resistance of copper steel and iron - Copper in cast iron - Copper in complex steels and other alloys - Copper-rich alloys.